Sensible salts, sugars, and fats - Marsico, Katie, 1980- (Ann Arbor, Michigan : Pebble, a Capstone imprint, 2021)
"Fat, salt, and sugar are a flavor food, not a food group. Learn how much of these flavor foods you should eat to stay healthy and maintain a healthy diet. Content encourages balance and making healthy choices. This level 3 guided reader is based on the U.S. government's diet recommendations. Readers will develop word recognition and reading skills while learning about food and where it comes from. Includes table of contents, glossary, index, author biographies, and word list for home and school connection"
Includes bibliographical references (page 31) and index.
Keywords: Nutrition -- Juvenile literature